Androgen changes and flexible rutting behaviour in male giraffes - Seeber, Peter A. (The Royal Society, 2013)
The social organization of giraffes (Giraffa camelopardalis) imposes a high-cost reproductive strategy on bulls, which adopt a ‘roving male’ tactic. Our observations on wild giraffes confirm that bulls indeed have unsynchronized rut-like periods, not unlike another tropical megaherbivore, the elephant, but on a much shorter timescale. We found profound changes in male sexual and social activities at the scale of about two weeks. This so far undescribed rutting behaviour is closely correlated with changes in androgen concentrations and appears to be driven by them. The short time scale of the changes in sexual and social activity may explain why dominance and reproductive status in male giraffe in the field seem to be unstable.